Long‐term survival after hepatic and pulmonary resection of colorectal cancer metastases. Issue 4 (26th July 2013) - Sourrouille, Isabelle; Mordant, Pierre; Maggiori, Léon; Dokmak, Safi; Lesèche, Guy; Panis, Yves; Belghiti, Jacques; Castier, Yves
Abstract Background Recent changes in adjuvant therapies improved the prognosis of metastatic colorectal cancers. Curative resection may be considered, even for both pulmonary and hepatic metastases, but prognostic factors are not well identified. Methods From 1995 to 2010, 69 patients had curative resection of pulmonary metastases of colorectal cancer; 31 had also hepatic metastases. Pulmonary and hepatic resection occurred in 2 steps (87%). We studied overall and disease‐free survival and prognostic factors. Results Primary tumor location was the rectum in 10 cases (32%). Pulmonary metastases were synchronous in 5 (16%) and bilateral in 6 (19%). One patient (3%) died after pulmonary surgery. One (3%) had positive surgical margins for pulmonary metastases. Median overall survival was 44 months (5‐year rate = 36%); median disease‐free survival was 22 months (5‐year rate = 10%). Factors linked to impaired survival were rectal primary tumor (P = 0.04) and bilateral pulmonary metastases (P = 0.02) for overall survival, and pulmonary metastase≥20 mm (P = 0.04) for disease‐free survival. Conclusion When associated to adjuvant therapy, complete resection of pulmonary and hepatic metastases of colorectal cancer allows long‐term survival in one third of the patients. J. Surg. Oncol. 2013 108:220–224. © 2013 Wiley Periodicals, Inc.